2015
DOI: 10.1002/acr.22498
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Ulceration in Dermatomyositis: Association With Anti–Melanoma Differentiation–Associated Gene 5 Antibodies and Interstitial Lung Disease

Abstract: Objective To identify clinical and serologic correlates of cutaneous ulcers in dermatomyositis (DM). Methods We retrospectively examined a cohort of 152 DM patients. We compared the features of patients with ulcers to those without ulcers using chi-square or Fisher’s exact tests and used univariate and multivariate logistic regression models to assess the association between ulcers and clinical features such as malignancy, interstitial lung disease (ILD), and amyopathic disease. Results Forty-three patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 25 publications
9
117
3
6
Order By: Relevance
“…A Japanese dermatomyositis cohort showed that skin ulcers are associated with reduced survival, and that the majority of these patients died of ILD 29 . A study has confirmed the strong association between anti-MDA5 antibodies and cutaneous ulcers 28 , and that ulcers are associated with the presence of ILD primarily in anti-MDA5-positive patients.…”
Section: Rheumatologymentioning
confidence: 85%
See 2 more Smart Citations
“…A Japanese dermatomyositis cohort showed that skin ulcers are associated with reduced survival, and that the majority of these patients died of ILD 29 . A study has confirmed the strong association between anti-MDA5 antibodies and cutaneous ulcers 28 , and that ulcers are associated with the presence of ILD primarily in anti-MDA5-positive patients.…”
Section: Rheumatologymentioning
confidence: 85%
“…However, true vasculitis with fibrinoid necrosis of vessel walls and leukocytoclastic figures was observed in only 3% of the patients with skin necrosis or ulcers. Most of these cases showed obliterative microvasculopathy, such as thickening of vascular wall obstruction or narrowing of vascular lumen or perivascular lymphocytic infiltration 26,28 . In our study, skin biopsy of ulcerative Gottron papules/Gottron sign confirmed the presence of vasculopathy and intraluminal thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiorentino et al showed that skin ulcerations, palmar papules (inverse Gottron), mechanic's hands, Gottron sign (elbow/knee), hand swelling, diffuse hair loss, panniculitis, and oral pain and/or ulcers were associated with this antibody [36]. They also demonstrated a strong association between location of skin ulcer at the digital pulp/periungual region and this antibody in a subsequent study [37]. Anti-MDA5 antibodies were associated with ILD largely in patients with skin ulcers.…”
Section: Anti-mda5 Antibodymentioning
confidence: 85%
“…[6][7][8][9][10][11] Anti-MDA5-positive-DM patients typically present with prominent skin manifestations, including heliotrope rash, Gottron's papules as well as cutaneous ulceration and tender palmar papules, the latter of which are unique to anti-MDA5-positive-DM (Table 1). 6,[12][13][14] Oral manifestations-including oral ulceration, mucosal pain, and hoarseness-are common, as are arthritis, arthralgia, and fever. 6,7,9,15 This patient initially • Mucosal pain • Alopecia had fever and later developed hoarseness, pharyngeal ulceration, arthritis, and arthralgia.…”
Section: Discussionmentioning
confidence: 99%